2017
DOI: 10.1007/s11882-017-0723-0
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use and Smoke Exposure in Children: New Trends, Harm, and Strategies to Improve Health Outcomes

Abstract: Twelve-20% of women continue to smoke during pregnancy. New research reveals cognitive differences and behavior-control disorders are seen in elementary school children from prenatal and postnatal exposures. Traditional cigarette smoking has decreased in adolescents; novel and appealing tobacco products have captured their attention, particularly electronic cigarettes, and rates double and often triple from middle to high school. Children with asthma and those living in multi-housing units have higher rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 106 publications
0
55
0
Order By: Relevance
“…Nicotine use by pregnant women is associated with increased risk of behavioral disorders, not only in their children but also in multiple generations of descendants [ 1 5 ]. Whereas maternal nicotine use is an undeniable concern, in reality more men smoke cigarettes than women [ 6 , 7 ]. Studies in human subjects suggest that paternal cigarette smoking adversely impacts attentional control [ 8 ] and increases the risk for attention deficit hyperactivity disorder (ADHD) in the offspring [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine use by pregnant women is associated with increased risk of behavioral disorders, not only in their children but also in multiple generations of descendants [ 1 5 ]. Whereas maternal nicotine use is an undeniable concern, in reality more men smoke cigarettes than women [ 6 , 7 ]. Studies in human subjects suggest that paternal cigarette smoking adversely impacts attentional control [ 8 ] and increases the risk for attention deficit hyperactivity disorder (ADHD) in the offspring [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that inhaling second-hand smoke (SHS) is harmful and that no scientific evidence establishes a risk-free level of exposure. 1 2 Notably, a retrospective analysis of data from 192 countries revealed that 40% of children (including 35% of non-smoking women and 33% of non-smoking men) were exposed to SHS, and this exposure is estimated to result in an annual estimate of 603 000 deaths attributable to SHS. 3 Global youth tobacco surveillance also reported that nearly half the adolescents worldwide were exposed to SHS at home (42.5%) and in public places (55.1%), which constitutes a substantial public health threat and demands urgent intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco smoking and drinking alcohol have been confirmed as associated with many chronic diseases [36][37][38][39], and to adversely affect the health of children [40,41]. Therefore, more effective measurements should be conducted to make children more aware of the harm of smoking and alcohol drinking on health.…”
Section: Discussionmentioning
confidence: 99%